Desertathrips chuquiraga gen. et sp.n. (Thysanoptera, Thripidae) from Argentina - de Borbón, Carlos Manuel (Zootaxa, 2008)
A new genus and species of Thripidae, Desertathrips chuquiraga, is described from Mendoza, Argentina, from the flowers of the endemic plant Chuquiraga erinacea (Asteraceae). Similar to Anaphothrips species in lacking any long pronotal setae, this species is one of a small group of Neotropical Thripinae in which males have a glandular opening between the second and third abdominal sternites. A check-list is included of 120 Thysanoptera species in 69 genera recorded from Argentina.